Lifestyle and factors of vascular and metabolic health and inflammation are associated with sensorineural-neurocognitive aging in older adults - Merten, Natascha; Fischer, Mary E.; Pinto, Aaron Alex; Chappell, Richard J.; Schubert, Carla R. (Frontiers in Epidemiology, 2024)
This study’s aim was to identify risk factors associated with sensorineural and neurocognitive function (brain aging) in older adults. In N=1478 Epidemiology of Hearing Loss Study participants (aged 64-100 years,59% women), we conducted sensorineural and cognitive tests, which were combined data into a summary measure using Principal Component Analysis (PCA). Participants with a PCA score<-1 standard deviation (SD) were considered to have brain aging. Incident brain aging was defined as PCA score<-1 SD at 5-year follow-up among participants who had a PCA score≥-1SD at baseline. Logistic regression and Poisson models were used to estimate associations between baseline risk factors of lifestyle, vascular and metabolic health, and inflammation and prevalent or incident brain aging, respectively. In an age-sex adjusted multivariable model, not consuming alcohol (odds ratio(OR)=1.77, 95% confidence Interval (CI)=1.18,2.66), higher interleukin-6 levels (OR=1.30, 95% CI=1.03,1.64), and depressive symptoms (OR=2.44, 95% CI=1.63,3.67) were associated with a higher odds of having brain aging, while higher education had protective effects (OR=0.55, 95% CI=0.33,0.94). A history of stroke, arterial stiffness, and obesity were associated with an increased risk of developing brain aging during the five years of follow-up. Lifestyle, vascular, metabolic and inflammatory factors were associated with brain aging in older adults, which adds to the evidence of shared pathways for sensorineural and neurocognitive declines in aging. Targeting these shared central processing etiological factors with interventions may lead to retention of better neurological function, benefiting multiple systems, i.e., hearing, smell, and cognition, ultimately helping older adults retain independence and higher quality of life longer.